Variation in competence for ZIKV transmission by Aedes aegypti and Aedes albopictus in Mexico - Armstrong, Philip M.; García Luna, Selene Marysol; Weger Lucarelli, James; Rückert, Claudia; Murrieta, Reyes A.; Young, Michael C.; Byas, Alex D.; Fauver, Joseph R.; Perera, Rushika; Flores Suárez, Adriana Elizabeth; Ponce García, Gustavo; Rodríguez Ramírez, Américo David; et al. (Public Library of Science, 2018)
Abstract Background ZIKV is a new addition to the arboviruses circulating in the New World, with more than 1 million cases since its introduction in 2015. A growing number of studies have reported vector competence (VC) of Aedes mosquitoes from several areas of the world for ZIKV transmission. Some studies have used New World mosquitoes from disparate regions and concluded that these have a variable but relatively low competence for the Asian lineage of ZIKV. Methodology/Principal findings Ten Aedes aegypti (L) and three Ae. albopictus (Skuse) collections made in 2016 from throughout Mexico were analyzed for ZIKV (PRVABC59—Asian lineage) VC. Mexican Ae. aegypti had high rates of midgut infection (MIR), dissemination (DIR) and salivary gland infection (SGIR) but low to moderate transmission rates (TR). It is unclear whether this low TR was due to heritable salivary gland escape barriers or to underestimating the amount of virus in saliva due to the loss of virus during filtering and random losses on surfaces when working with small volumes. VC varied among collections, geographic regions and whether the collection was made north or south of the Neovolcanic axis (NVA). The four rates were consistently lower in northeastern Mexico, highest in collections along the Pacific coast and intermediate in the Yucatan. All rates were lowest north of the NVA. It was difficult to assess VC in Ae. albopictus because rates varied depending upon the number of generations in the laboratory. Conclusions/Significance Mexican Ae. aegypti and Ae. albopictus are competent vectors of ZIKV. There is however large variance in vector competence among geographic sites and regions.